FRI0621-HPR Reference Values for The Modified Functional Reach Test in Younger and Middle-Aged Turkish Population - Yuksel, E.; Ilgin, D.; Kul Karaali, H.; Ozcan, O.; Unver, B. (Annals of the rheumatic diseases, 2016)
BackgroundModified Functional Reach Test (MFRT) is reliable, precise, and less time-consuming for detecting dynamic sitting balance (1). Normative data for this measurement tool have been reported in Indian and American population (1,2). Reference values for MFRT are not available in Turkish population.ObjectivesOur aim was to establish reference values for the MFRT to examine the effect of gender and various anthropometric measurements on MFRT in healthy younger and middle-aged Turkish populationMethodsEthics approval for this study was obtained from the Ethics Committee of Celal Bayar University. Informed consent was obtained from all participants in accordance with the Declaration of Helsinki before participation.Participants (employee and academic staff) were recruited from Celal Bayar University campus. Permission was obtained from authorities of the University to carry out the study. Therefore, 462 participants within the age range of 20 to 59 years successfully included to the study and completed all necessary process. Based on the literature, these participants were stratified into 2 age groups; younger age group (ages 20–39 years) and middle age group (ages 40–59 years). There were 278 people in the younger age group and 184 people in the middle-aged group.Prior to testing, the participants were screened based on inclusion criteria: both gender without balance problems, healthy subjects and 120 of shoulder flexion and abduction range of motion to perform the reach tests. Participants were excluded based on following criteria: any neurological disorder, balance disorder and any treatment for an ear infection within the past 6 weeks.ResultsFor younger age group, the reference value of forward reach was 41.8±11.9 cm and reference values for lateral right and left reach were 30.9 ± 9.5 cm and 30.5 ± 9.5 cm, respectively. For middle-aged group, the reference values of forward, lateral right and left reach were 46.3± 12.4 cm, 33.1±10.5 cm and 32.9±10.8 cm, respectively. There is no significant differences between male and female in terms of all scores in each group. Anthropometric characteristics were similar in both age groups.ConclusionsAlthough these reference values are similar with American populations, the mean MFRT scores for younger and middle aged Turkish population are higher than same age Indian population, especially reference values of lateral reaches. These normative data will be also useful to researchers and clinicians in the sitting balance assessment in the Turkish population.ReferencesLynch SM, Leahy P, Barker SP. Reliability of measurements obtained with a modified functional reach test in subjects with spinal cord injury. Phys Ther 1998;78:128–33.Singh P, Hujon N. Normative data of Modified Functional Reach Test in younger and middle-aged North Eastern Indian population. Arch Med Health Sci 2013;1:109–14.Disclosure of InterestNone declared